Asosiasi Pemberian MP-ASI terhadap Status Gizi Anak di Daerah Lokus Stunting di Mamuju - Yudianti Yudianti; Hapzah Hapzah; Nurbaya Nurbaya (Politeknik Kesehatan Kemenkes Mamuju, 2022)
West Sulawesi is the second province with the highest stunting rate, above the national average of 41.59%, based on the 2018 Basic Health Research data. In 2019 it decreased to 40.38%. However, this figure is still below the national target. Maternal parenting and giving MP-ASI that are less than optimal are among the main causes of stunting. This study aims to determine the factors that cause stunting while providing complementary feeding to children under five in the stunting locus area in Mamuju Regency, West Sulawesi. This research method is quantitative research with a cross-sectional design. Random sampling selected the number of samples, as many as 130 under-two children aged 6-13 months. Data were processed using the chi-square test and multivariate analysis using the logistic regression test. This study shows that the pattern of giving complementary feeding to children aged 6-23 months is still low. The pattern of giving MP-ASI from the type, amount, and time of giving MP-ASI was still lacking, namely 72.3%, 80%, and 45.8%, respectively. There was a relationship between the type of complementary feeding and stunting (ρ<0.05, OR 2.590 ). So education and counseling activities regarding Infants and Young Children Feeding (IYCF) need to be intensified, especially for mothers in the stunting locus area.